2012
DOI: 10.2971/jeos.2012.12039
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index sensor based on slot waveguide cavity

Abstract: The experimental study of a gold slot waveguide cavity is presented. The resonance of this cavity working in the telecom wavelength range is highly dependent on the refractive index of the medium located in or around the slots array, because of the high confinement of the electromagnetic field in the structure. We will demonstrate the application of this structure to local refractive index sensors at the nanoscale. The measured sensitivity of this device is S = 730 nm/RIU (refractive index unit). The structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“…The bulk sensitivity values obtained by our simulations are only 40% lower than the result shown in [4] where a periodic array of PSWC is used on top of a slab waveguide which also has a 30 times larger interaction volume. As the goal of this sensor is to detect the binding of small molecules to its surface, a high bulk sensitivity might create a lot of noise to the detection e.g.…”
Section: Bulk and Local Sensitivitycontrasting
confidence: 71%
See 1 more Smart Citation
“…The bulk sensitivity values obtained by our simulations are only 40% lower than the result shown in [4] where a periodic array of PSWC is used on top of a slab waveguide which also has a 30 times larger interaction volume. As the goal of this sensor is to detect the binding of small molecules to its surface, a high bulk sensitivity might create a lot of noise to the detection e.g.…”
Section: Bulk and Local Sensitivitycontrasting
confidence: 71%
“…In this paper we propose a geometry, based on a plasmonic slot waveguide cavity, that enables a significant improvement of highly multiplexed detection on an integrated silicon platform [4,5]. Due to the large enhancement of the electromagnetic field by the SPP, the sensing volume is highly reduced, which allows localized detection of molecules in sub-attoliter volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Having this aim in mind, here we present a theoretical study of a refractive index sensor which is based on a plasmonic slot waveguide cavity (PSWC) excited by a photonic wire waveguide sustaining a single mode. In this manuscript we search for a stronger localization than introduced in our previous work which was a PSWC array excited with a slab waveguide 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of the SWG by Lipson [5], world-wide efforts have been made in investigating SWG for various applications, notably in nonlinear effect enhancement [6,7] and highly sensitive sensors [8,9]. Most often, SWG is combined with active materials such as EO polymers or with photonic crystals (PhCs) in order to obtain the desired functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nanometric size, SWG oftentimes combines with 1D PhC Bragg gratings to design active optical components. In [8], a gold film slot Bragg grating on a silicon WG is proposed as a refractive index sensor with a sensitivity of 730 nm∕RIU. Wang et al experimentally demonstrated a phased-shifted Bragg grating with a quality factor up to 3 × 10 4 fabricated by a CMOS-compatible fabrication technique [9].…”
Section: Introductionmentioning
confidence: 99%